Nestor, Barbara (audio interview #9 of 10) - Nestor, Barbara (9/29/1884 - 11/1/1979); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This eighth interview with Barbara Nestor took place more than six weeks after the previous one, after she recovered from a severe case of the flu. In contrast to previous interviews, there was some evidence of poorer hearing as well as a memory problem. She also seemed to have difficulty grasping the questions. Her voice sounds mumbled on the first side of the tape (8a) and there are skips in the recording in a few segments on the second side (8b). 2/25/1975